The Effect of Economic Growth on the Utilisation of Childhood Immunisation: New Evidence From 50 African Countries - Mustapha Immurana; Abdul Mumin Abdul Rahman (SAGE Publishing, 2024)
Africa bears the greatest brunt of under-five mortality in the world. Among the major approaches used in tackling under-five deaths is childhood immunisation. While income is regarded as a major determinant of demand for child health inputs including immunisation, the existing studies are microlevel analyses, which do not provide a bigger picture of how an enhancement in economic growth (aggregate income) contributes to the utilisation of childhood immunisation in an economy as a whole. Since Africa has experienced economic growth in the recent decades, this study aims to fill this gap in the literature by examining the contribution of economic growth to the utilisation of childhood immunisation in selected African countries. The study uses a panel design involving data on 50 African countries over the period, 2002 to 2019. Utilisation of DPT (diphtheria, pertussis (or whooping cough) and tetanus) and measles immunisation are used as proxies for childhood immunisation while the system Generalised Method of Moments (GMM) regression is used as the estimation technique. We find economic growth to have a positive significant effect on the utilisation of childhood immunisation. Thus, it is imperative to intensify the enablers of economic growth in Africa in order to increase the utilisation of childhood immunisation.